Le Dictionnaire québécois d’aujourd’hui : Enquête sur les registres - Guillot, Marie-Cécile (Canadian Journal of Applied Linguistics, 1999)
The Dictionnaire québécois d’aujourd’hui came out in 1992. The publication of this dictionary sparked a controversy on, among other things, word labeling. The language registers given for many words did not seem to reflect how Quebec francophones felt about them. The debate was such that, one year later, a second edition was produced. The main changes made concern the language registers of a number of entries, on which this time, Quebec francophones would agree. A survey was therefore carried out to determine whether the registers indicated in Le Dictionnaire québécois d’aujourd’hui correspond to Quebec francophones’ linguistic intuitions. A 50-word questionnaire was given to 150 respondents, who were asked to assign a language register to each word. The results of this survey have led to the conclusion that the registers given in Le Dictionnaire québécois d’aujourd’hui often do not correspond to the intuitions of Quebec francophones.